Adaptive co-site interference cancellation algorithm with multiple virtual references - Yue-lei XIE; Jie LIU; Min-zheng LI; Shan OUYANG; Gui-sheng LIAO (Tongxin xuebao, 2015)
Wireless radio communication is usually deteriorated by co-site interferences produced by collocated transmitters.A two-stage adaptive filter with multiple virtual references that drew from over sampled receiving signal is proposed to cancel the co-site interferences.Co-site interferences can be cancelled and the desired signal can be recovered by adjusting the weights of the first filter when pure interferences are received and adjusting the weights of the second filter when the desired signal is consisted in received signals.The simulation results show that the proposed adaptive co-site interferences cancellation algorithm without the coupling device can achieve better performance than traditional algorithms.